Identification of a 145,000 Mr membrane protein as the C3d receptor (CR2) of human B lymphocytes. - Weis, J J (1984)
The C3d receptor (CR2) of human B lymphocytes mediates the binding to these cells of immune complexes that have activated the complement system and bear the fragments of C3, iC3b, C3d,g, and C3d. A 145,000 Mr membrane protein previously described as being recognized by the monoclonal antibody HB-5 and shown to be expressed only by B lymphocytes and B lymphoblastoid cell lines, such as Raji, was assessed for its possible identity as CR2. Treatment of Raji cells with HB-5 and goat F(ab')2 anti-mouse IgG (GaM) diminished the capacity of these cells to form rosettes with sheep erythrocyte (E) intermediates bearing 130,000 molecules of iC3b or C3d, whereas treatment with the monoclonal antibody alone had no effect. The capacity of peripheral blood B lymphocytes to bind EC3d was similarly inhibited by the combination of HB-5 and GaM. The possibility that HB-5 may interact with a site on CR2 that is distinct from the ligand binding site permitted the direct analysis of the capacity of the HB-5 antigen to bind to the C3 fragments. Protein A-containing Staphylococcus aureus particles to which HB-5 had been bound were incubated with detergent lysates of Raji cells and B lymphocytes under conditions that had been shown to be associated only with the binding of the 145,000 Mr antigen. These particles bearing HB-5 and antigen derived from either cell type were shown to adhere specifically to EiC3b and EC3d, demonstrating that transfer of the HB-5 antigen from CR2-bearing cells to S. aureus particles led to the acquisition of CR2 function by the particles. The additional findings that the relatively weak capacity of Raji cells to form rosettes with EC3b was inhibited by HB-5 and that the S. aureus particles bearing immunoadsorbed HB-5 antigen bound to EC3b indicated that the C3b-binding function of the CR1-negative Raji cell resides in CR2, rather than in other membrane proteins.